Your many faces : the first step to being loved - Satir, Virginia (New York : Celestial Arts, 2009)
"A self-help guide about understanding and accepting the many facets of one's own personality, written by a distinguished American psychotherapist"--Provided by publisher.
Keywords: Self-perception.; Self-actualization (Psychology)